Comparative Transcriptome Analysis Demonstrates the Positive Effect of the Cyclic AMP Receptor Protein Crp on Daptomycin Biosynthesis in Streptomyces roseosporus - Wu, Jiequn; Chen, Danqing; Wu, Jinrong; Chu, Xiaohe; Yang, Yongmei; Fang, Lina; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2021)
Daptomycin, which is produced by Streptomyces roseosporus, has been characterized as a novel cyclic lipopeptide antibiotic that is effective against Gram-positive bacteria. The biosynthesis of daptomycin is regulated by various factors. In the present study, we demonstrated that the cyclic AMP receptor protein (Crp) plays an important role in producing daptomycin in the S. roseosporus industrial strain. We found that daptomycin production from the crp deletion strain decreased drastically, whereas production from the crp overexpression strain increased by 22.1%. Transcriptome and qPCR analyses showed that some genes related to the daptomycin biosynthetic gene cluster (dpt) and the pleiotropic regulator (adpA) were significantly upregulated. RNA-seq also shows Crp to be a multifunctional regulator that modulates primary metabolism and enhances precursor flux to secondary metabolite biosynthesis. These results provide guidance for the development and improvement of potential natural products.